2021
DOI: 10.3390/biomedicines9070814
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vancomycin Delivery Systems Based on Autologous 3D Platelet-Rich Fibrin Matrices for Bone Tissue Engineering

Abstract: Autologous platelet-rich fibrin (PRF) is derived from the blood and its use in the bone tissue engineering has emerged as an effective strategy for novel drug and growth factor delivery systems. Studies have approved that combined therapy with PRF ensures higher biological outcomes, but patients still undergo additional treatment with antibiotic drugs before, during, and even after the implantation of biomaterials with PRF. These systematically used drugs spread throughout the blood and lead not only to positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…I-PRF without the addition of antibiotics served as a control group. A sustainable antibiotic release was only shown in group I when antibiotics were added to the fabricated i-PRF before clot was formed [32,36]. Another study by Polak et al depicted antibacterial properties of PRF, when patients´ blood is incorporated with antibiotic drugs before the centrifugation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I-PRF without the addition of antibiotics served as a control group. A sustainable antibiotic release was only shown in group I when antibiotics were added to the fabricated i-PRF before clot was formed [32,36]. Another study by Polak et al depicted antibacterial properties of PRF, when patients´ blood is incorporated with antibiotic drugs before the centrifugation process.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is different when a specific antibiotic is desired, but systemically application is not possible, for example, when the side effects exceed the positive benefit or when it is a reserve antibiotic, as with vancomycin or gentamicin. In those cases, the incorporation of patient's blood after blood sampling could be beneficial 1 3 [20,21,32,33,36,37]. Different approaches for antibiotic instillation are described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting fibrin–polysaccharide composite gel is convenient to use, as it allows implantation in a liquid form, followed by in situ hardening, but can also be used orally in the form of preformatted capsules, since it showed high resistance to the acidic pH of the stomach. The absence of a toxic effect on normal cells of its ingredients, these being fibrin and rhamnogalacturonan I (potato galactan), as well as DPPC liposomes, was previously established [ 11 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using fibrin clots as a drug carrier has been studied in a number of works [ 31 , 32 , 33 ]. It was shown that the drug retention time depends on the pore size, the resistance of the fibrin matrix to the external environment, and the interaction of the drug with fibrin.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of VANKA release in the PRF/PLGA_µC_VANKA scaffold was reduced two-fold relative to the PLGA_µC_VANKA scaffold, indicating that PRF inhibited the rapid release of VANKA. This delivery system ensures controlled VANKA release for 6 ∼ 10 days, with the full antimicrobial effect lasting 48 h ( Dubnika et al, 2021 ). Anton Straub et al collected blood from subjects 10 min after intravenous injection of ampicillin/sulbactam and prepared PRF by centrifugation; the antibiotic concentration in PRF was comparable to the blood concentration, and PRF scaffolds loaded with ampicillin/sulbactam showed significant antibacterial effects against Haemophilus influenza , Staphylococcus aureus , and Streptococcus pneumoniae ( Straub et al, 2022 ).…”
Section: Application Of Prf In Bone Tissue Engineeringmentioning
confidence: 99%